Accounting information systems in Indonesia: a case study / Poni Sukaesih Kurniati and Suryanto - Kurniati, Poni Sukaesih; Alias, Suryanto (Universiti Teknologi MARA, 2021)
This research aimed to analyze local government accounting information systems in Indonesia. The research was conducted in Bandung, West Java, Indonesia. This research used a qualitative approach where data was collected from in-depth interviews, observations, and review of documents. The results showed that the accounting policies undertaken by the Government of Bandung City were not in accordance with Government Accounting Standards as regulated in the Government Regulation No. 71 of 2010. Accounting policies undertaken by the Government of Bandung were carried out through two stages: accounting for financial reporting and accounting policies. The application of accounting information systems is able to produce useful local government financial statements for users in assessing accountability and making decisions in both economic, social and political decisions. However, in its implementation even though there is an accounting information system, there is still overlap in the use of the accounting base. This research can add to the accounting information system literature, especially regional government accounting information systems. In addition, the results of this study are important in measuring the application of government accounting standards